Establishing the link between fibril formation and Raman optical activity spectra of insulin. Issue 21 (19th May 2017) - Kessler, Jiří; Yamamoto, Shigeki; Bouř, Petr
Abstract : Molecular dynamics and density functional simulations are used to explain changes in Raman optical activity accompanying the formation of insulin fibrils. Abstract : Folding of proteins into insoluble amyloidal fibrils is implicated in a number of biological processes. Optical spectroscopy represents a convenient tool to monitor such structural variations. Recently, characteristic changes in Raman optical activity (ROA) spectra of insulin during a pre-fibrillar stage were reported but not supported by a theoretical model. In the present study, molecular dynamics and the density functional theory are used to simulate the spectra and understand the connection between the structure, and ROA and Raman spectral intensities. Theoretical results are consistent with the observations and only confirm exceptional ROA sensitivity to the protein tertiary structure. Surprisingly, this sensitivity reflects local conformational changes in the peptide main and side chains, rather than a direct through-space interaction of the protein components. Side chains providing strong ROA signals, such as tyrosine, can additionally report on local conformational features. Theoretical modeling helps in explaining the observed spectral changes and is likely to enable future applications of ROA spectroscopy in protein structural studies.